Cyber Security Analysis and Law; Bjorka Case - Prasetyo, Aldiyan Harun (Journal of ASEAN Dynamics and Beyond, 2022)
Technology has always been a powerful tool for advancing human civilization. It had allowed us more organized, efficient, and connected. Since the dawn of the Internet, we have increasingly relied on electronic communications as a means of doing business. Cybersecurity, which also encompasses authentication, non-repudiation (non-denial), and accountability, is an effort to safeguard the confidentiality, integrity, and accessibility of information in cyberspace. The process of defending computers, servers, mobile devices, electronic systems, networks, and data from hostile attacks falls under the category of cybersecurity. The following questions are used to evaluate the descriptive data in this paper, which employs a qualitative management approach: What prompted hackers to inflitrate Indonesia and How is the government responding.